Influence of the Contextual Teaching and Learning Model on Student Learning Activities and Learning Outcomes on Ecosystem Material in Cluster II Sungai Penuh - Siti Fatimah Azzahrah; Muhammadi; Yanti Fitria; Abna Hidayati (Postgraduate, University of Mataram, 2026)
This research is motivated by the fact that low learning activities also affect student learning outcomes in science learning in elementary schools. Students are less active in the learning process, both in expressing opinions, asking questions, and constructing their own knowledge. Students tend to wait for direction from the teacher, and only a few are actively involved in group discussions. One effort that can be done is to use the CTL learning model. This study aims to determine the effect of the CTL learning model on learning activities and student learning outcomes in the ecosystem material in cluster II Sungai Penuh.The type of research used Is Quasi Experimental. The research population was students of Elementary School Cluster II Sungai Penuh. The sample of this research was students of class Va SDN 025/XI Gedang Village Sungai Penuh as the experimental class and students of class Vb SDN 001/XI Sungai Penuh as the control class. The instruments used in this research were learning activity questionnaires and learning outcome test sheets. The data analysis technique used prerequisite tests in the form of normality and homogeneity tests. Meanwhile, to test the hypothesis using an independent t test. To determine the relationship between learning activities and learning outcomes, a correlation test was carried out. The results of this study indicate that there is an influence of the CTL learning model on learning activities and student learning outcomes on ecosystem material in cluster II of the full river. The details of the data analysis results are: (1) The CTL learning model improves student learning outcomes by linking lesson materials to everyday life so that concepts are easier to understand, as evidenced by the results of the study which obtained a significance value of 0.000 for the posttest. By taking a significance value of 5%, it is concluded that H0 of this study is rejected, while H1 is accepted, meaning that there is an influence of the CTL learning model on student learning activities. (2) The CTL learning model improves student learning activities, as seen from active involvement in discussions and completing assignments, as evidenced by the results of the study which obtained a significance value of 0.000 for the posttest. By taking a significance value of 5%, it is concluded that H0 of this study is rejected, while H1 is accepted, meaning that there is an influence of the CTL learning model on student learning outcomes. (3) There is an influence of learning activities on student learning outcomes by using the CTL learning model. This increase in learning activities contributes to an increase in learning outcomes, showing a positive influence between the two.